ANALISIS PENGARUH SUHU TERHADAP PERFORMANSI OPEN CATHODE PROTON-EXCHANGE MEMBRANE FUEL CELL (OCPEMFC) - Teofilus R.M. Silalahi; Waru Djuriatno; Eka Maulana (Jurnal Mahasiswa TEUB, 2023)
The Open Cathode Proton-Exchange Membrane Fuel Cell (OCPEMFC) is a promising technology for generating clean and efficient electrical energy. However, the performance of OCPEMFC is influenced by various factors, including the operational temperature range. The performance also depends on the chemical reactions occurring between hydrogen and oxygen with water, with electricity and heat produced as reaction products. In the reaction process of OCPEMFC, the rate and quality of oxygen supply to the cathode play a crucial role in enhancing the performance of OCPEMFC. This research aims to analyze the influence of temperature on OCPEMFC performance. OCPEMFC is a technology capable of producing environmentally friendly and efficient electrical energy. However, the performance of OCPEMFC can be affected by the operational temperature range. This study utilizes a system specifically designed to support temperature measurements using the DS18B20 sensor. The use of a blower in analyzing the temperature's effecton OCPEMFC performance is one solution to maintain the operational temperature range of OCPEMFC, which also affects the oxygen flow rate to the cathode. The application of a blower with Pulse Width Modulation (PWM) control is a solution to maintain the operational temperature range of OCPEMFC. The PWM value on the blower directly influences the generated airflow rate. PWM control allows adjusting the airflow to maintain the desired operational temperature. By increasing the blower speed, the oxygen flow rate can be enhanced, improving the efficiency of electrochemical reactions inside OCPEMFC. The use of a blower to control the temperature of OCPEMFC can help improve its performance, extend its lifespan, and support its use in cleaner and more sustainable energy applications. Keywords: FUEL CELL, BLOWER, TEMPERATURE, DS18B20 sensors , PWM